DAMPAK METODE PERPETUAL DAN PENILAIAN PERSEDIAAN TERHADAP NILAI PERSEDIAAN ALAT LABORATORIUM LAINNYA PADA BADAN NARKOTIKA NASIONAL KOTA PONTIANAK - Agustini, Sari Rusmita (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2016)
This study aimed to find out how theimpact of perpetual method and the inventory valuation method against value of inventory at the end of the other laboratory equipments in Badan Narkotika Nasional city of Pontianak.The research method used is descriptive qualitative with research object is supplies of other laboratory equipment in BNN city of Pontianak. The data used is the balance sheet and inventory report 2014 as well as other necessary data. Data collection techniques are study documentation, observations (observation) and interviews. Data analysis tool used is the Organizational Structure and Minister of Finance regulation No. 219 / PMK.05 / 2013 on Central Government Accounting Policy. According to analysis carried out it can be concluded that the recording of inventory on BNN city of Pontianak using the perpetual method. Perpetual methods impact the effective and efficient for the management of goods inventory ministry / agency, because this method can provide quick and accurate information on the balance of goods at any time and at the time of Taking Stock. The final valuation of inventory items on BNN Pontianak City which last cost method. The impact of the last cost method that could lead to deviation, because the value of inventory may be lower or higher than the actual value of the inventory in accordance with the final acquisition price of such supplies. This deviation will have an impact in the statement of financial position (balance sheet) that is the amount of inventory, current assets, total assets, inventory reserves and equity funds will be reported to higher smoothly anyway.Keywords: Inventory, Perpetual Method,Last cost Method, FIFO Method